Mandated counselling satisfaction, self efficacy and readness to change among institutionalised adolescent - Muhammad Shariff Paul, Azzah Sabrina; Abu Talib, Mansor (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Mandated counselling has emerged as one of approach helping profession in dealing with juvenile issues. Though there are successes in treating clients towards a positive behaviour, there are still a lot of relapse cases occurring among them. Hence, this study is to examine the relationship of mandated counselling satisfaction and behaviour change among institutionalised adolescent. A total of 365 respondents from six states which are Selangor, Melaka, Perak, Terengganu, Pahang and Sarawak were requited. The respondents were selected based three conditions; (a) adolescent aged 13 to 19 years old; (b) has attended mandated counselling at least twice; and (c) were involved in juvenile problem. The instrument used for this study is Mandated Counselling Satisfaction (MCgSS) that measure satisfaction in mandated counselling, General Self-Efficacy Scale (GSE) to measure self-efficacy and University of Rhode Island Change Assessment (URICA) for behaviour change in respondents. Pearson correlation analysis showed significant positive relationship between mandated counselling satisfaction, self- efficacy on readiness to change. Multiple regression analysis revealed mandated counselling satisfaction as the unique predictor towards readiness to change. In conclusion, it is important for counsellors to improve their skills and overall process of mandated counselling in order to promote behaviour change among mandated clients.